2014
DOI: 10.1002/etc.2722
|View full text |Cite
|
Sign up to set email alerts
|

The role of complexation and competition in the biouptake of europium by a unicellular alga

Abstract: Short-term (60 min) europium (Eu) biouptake fluxes by the freshwater green alga Chlamydomonas reinhardtii were investigated in the presence and absence of ligands (e.g., malic acid and citric acid) and a second rare earth metal, samarium (Sm). Data were interpreted in the context of the biotic ligand model, which uses experimentally determined stability constants to take into account the competition and complexation of the metal of interest. In the absence of ligands or competitors, Eu biouptake was well descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…While this observation has been validated on numerous occasions, several exceptions, where bioaccumulation or toxicity is significantly greater than can be predicted on the basis of the free ion alone, have also been noted in the literature. [13][14][15][16]27,41,42 For example, Slaveykova et al showed that Pb complexes with dissolved organic matter could contribute to the bioavailability of Pb to C. kesslerii. 41 In earlier work, we ascribed a greater than predicted toxicity of Al to Atlantic salmon to the formation of ternary complexes with Al−OH (K = 10 14.5 M −1 ) and Al−F (K = 10 13.5 M −1 ) at the fish gill surface (cf.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While this observation has been validated on numerous occasions, several exceptions, where bioaccumulation or toxicity is significantly greater than can be predicted on the basis of the free ion alone, have also been noted in the literature. [13][14][15][16]27,41,42 For example, Slaveykova et al showed that Pb complexes with dissolved organic matter could contribute to the bioavailability of Pb to C. kesslerii. 41 In earlier work, we ascribed a greater than predicted toxicity of Al to Atlantic salmon to the formation of ternary complexes with Al−OH (K = 10 14.5 M −1 ) and Al−F (K = 10 13.5 M −1 ) at the fish gill surface (cf.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When algae were exposed to similar demonstrated that the bioavailability of Ag was largely or completely reduced when algae were exposed to AgNO3 in a wastewater medium. The possible causes for reduced bioavailability in a wastewater medium include i) the complexation of Ag + ions by organic/inorganic ligands that render them non-bioavailable and ii) the presence of numerous ions in a wastewater medium that compete for Ag biouptake (competition) [42][43][44]. In contrast with the majority of previous studies where bioaccumulation experiments were conducted in simple growth media [18][19][20], Ag + bioavailability in the wastewater was greatly reduced due to the complex nature of the medium.…”
Section: Ag Bioavailability In the Wastewatermentioning
confidence: 99%
“…or a dissolution/precipitation mechanism (below 0.8 µM of sulfide), depending on the available sulfide concentrations [43]. …”
Section: Transformation Of Silver Nanoparticles In Wastewatersmentioning
confidence: 99%
“…Experiments using radiolabelled ligands can also show when ligands are not taken up by the organism. [45,47] In such cases, either an equilibrium or a kinetic explanation can be put forward to account for enhanced uptake. For example, for cases where metal adsorption-desorption kinetics are rate-limiting, the formation of the mixed-ligand complex at the cell surface (especially for inorganic ligands, such as hydroxide and chloride) can accelerate the water loss rate of the metal, thus increasing the rate of biouptake (mechanism 5 below).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of ternary complexes has been postulated to occur for both divalent metals, including Pb [43,49,50] and Zn, [44,51] and trivalent metals such as Al, [42,52] Sc, [53] Eu [47] and Tm. [45] Indeed, Aristilde et al [44] suggested that the formation of ternary complexes may be universal, irrespective of the specificity of the metal or ligand.…”
Section: Introductionmentioning
confidence: 99%